PENGARUH PERTUMBUHAN LABA DAN LIKUIDITAS TERHADAP KUALITAS LABA PT. ASIA SEJAHTERA MINA TBK TAHUN 2020-2022 - Christin Loria Pangaribuan; Agustim Jamal Lumban Tobing; Michael Alberto Butarbutar; Enjel Margaretha Br. Meliala; Rizki Christian Sipayung (Politeknik Negeri Ambon, 2023)
To determine the effect of profit growth on profit quality in trading companies listed on the Indonesia Stock Exchange in 2020-2022, to determine the effect of liquidity on profit quality in trading companies listed on the Indonesia Stock Exchange in 2020-2022. This study used the Descriptive Quantitative research method. The type of data the author uses is secondary data. This research was conducted from May 2023 to June 2023 at PT Asia Sejahtra Mina Tbk and used financial statement data of companies listed on the Indonesia Stock Exchange obtained through http://www.idx.co.id. The results of our research on PT. ASIA SEJAHTERA MINA, Tbk which is listed on the Indonesia Stock Exchange (IDX) shows that the profit growth of PT. ASIA SEJAHTERA MINA, Tbk did not have a significant impact on the quality of profits listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period, and the liquidity of PT. ASIA SEJAHTERA MINA, Tbk has a positive impact on the quality of profits listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. From this research PT. ASIA SEJAHTERA MINA, Tbk still cannot cover the liquidity of the profits generated, so the profit growth of this company still has to be improved. By improving product quality, improving the quality of the production/service process to allow for a reduction in the cost/burden of the production/service process, and also increasing the product/service production capability so that profits increase. The phrase to maybe wordy. Consider changing the wording.